The Psychological Horror & Psychoanalysis - LIMANTORO, Gray Hansen; ATMA, Yeyen Dwi (PT Batara Swastika Harati, 2024)
The horror genre is widely appreciated for its ability to challenge audiences through fear, offering suspense and excitement. Among its subgenres, psychological horror stands out for its unique focus on the mind, emotions, and internal struggles, rather than relying on direct confrontations with physical monsters or external threats. This subgenre delves into the complexities of the human psyche, often depicting mental illness and psychological tension to evoke fear. Unlike traditional horror, psychological horror builds suspense through atmosphere, character development, and the gradual unraveling of the protagonist's mental state, making it a subtler yet more unsettling form of horror. A literature review highlights how psychological horror has significantly shaped the portrayal of mental illness, offering deeper, more introspective representations of psychological disorders. The findings indicate that this subgenre's strength lies in its ability to present fear from a different perspective, often leaving much to the imagination of the audience, which intensifies the sense of dread. By focusing on internal fears and psychological conflicts, psychological horror provides a distinctive narrative experience, setting it apart from other horror subgenres that rely on physical confrontations. This makes it a compelling form of storytelling that resonates deeply with audiences, tapping into their subconscious fears and emotions